Assessment of a conduction-repolarisation metric to predict Arrhythmogenesis in right ventricular disorders. (15th November 2018) - Martin, C.A.; Orini, M.; Srinivasan, N.T.; Bhar-Amato, J.; Honarbakhsh, S.; Chow, A.W.; Lowe, M.D.; Ben-Simon, R.; Elliott, P.M.; Taggart, P.; Lambiase, P.D.
Abstract: Background: The re-entry vulnerability index (RVI) is a recently proposed activation-repolarization metric designed to quantify tissue susceptibility to re-entry. This study aimed to test feasibility of an RVI-based algorithm to predict the earliest endocardial activation site of ventricular tachycardia (VT) during electrophysiological studies and occurrence of haemodynamically significant ventricular arrhythmias in follow-up. Methods: Patients with Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) ( n = 11), Brugada Syndrome (BrS) ( n = 13) and focal RV outflow tract VT ( n = 9) underwent programmed stimulation with unipolar electrograms recorded from a non-contact array in the RV. Results: Lowest values of RVI co-localised with VT earliest activation site in ARVC/BrS but not in focal VT. The distance between region of lowest RVI and site of VT earliest site (Dmin ) was lower in ARVC/BrS than in focal VT (6.8 ± 6.7 mm vs 26.9 ± 13.3 mm, p = 0.005). ARVC/BrS patients with inducible VT had lower Global-RVI (RVIG ) than those who were non-inducible (−54.9 ± 13.0 ms vs −35.9 ± 8.6 ms, p = 0.005) or those with focal VT (−30.6 ± 11.5 ms, p = 0.001). Patients were followed up for 112 ± 19 months. Those with clinical VT events had lower Global-RVI than both ARVC and BrS patients without VT (−54.5 ± 13.5 ms vs −36.2 ± 8.8 ms, p = 0.007) and focal VT patients (−30.6 ± 11.5 ms, p = 0.002). Conclusions: RVI reliably identifies the earliest RV endocardial activation site of VT in BrS and ARVC but not focal ventricular arrhythmias and predicts the incidence of haemodynamically significant arrhythmias. Therefore, RVI may be of value in predicting VT exit sites and hence targeting of re-entrant arrhythmias. Highlights: A new Repolarisation Vulnerability Index (RVI) metric integrates dynamic changes in conduction and repolarisation. RVI predicts the earliest endocardial activation site of VT to a high degree of accuracy in Brugada Syndrome and ARVC. It also identified a population of patients more likely to develop haemodynamically unstable VT/VF over a 10 year follow-up period. RVI has the potential to guide ablation strategies in patients with unmappable VT.